Pemanfaatan Botol Plastik Bekas Sebagai Media Penanaman Bibit Tanaman pada Ibu-Ibu Pkk Desa Wonolopo, Mijen - Mukhlidin Mukhlidin; Alfin Muslikhun; Rowiyani Rowiyani; Jayus Jayus; Iqbal Maulana; Nita Nurmawati (FKIP, Universitas Palangka Raya, 2023)
Plastic bottles are a problem in society because every bottled drink after drinking, will become bottle waste. Bottle waste takes a very long time to decompose with the soil. So it needs to get special treatment so that it can be useful. Family Empowerment and Welfare Wonolopo village have a program to collect plastic waste for environmental cleanliness. Behind this environmental cleanliness, it turns out that plastic bottles can be used as a medium in planting plant seeds such as chili seeds, eggplant seeds, and tomato seeds. This community service activity is expected to be able to increase the spirit of independence and economy in Family Empowerment and Welfare to be able to utilize bottle waste so that it can be useful both in planting plants and reducing waste. The results of this activity are expected to increase self-awareness of plastic bottle waste pollution to be utilized for useful things. In addition, Family Empowerment and Welfare (PKK) can also reduce the kitchen shopping budget by utilizing bottle waste as a medium for planting chili, eggplant, and tomato plants.